Emotion and moral judgment. Issue 2 (3rd January 2013) - Avramova, Yana R.; Inbar, Yoel
Abstract Research in psychology and cognitive science has consistently demonstrated the importance of emotion in a wide range of everyday judgments, including moral judgment. Most current accounts of moral judgment hold that emotion plays an important role, but the nature and extent of this role are still debated. We outline three increasingly strong claims about the role of emotion in moral judgment and assess the evidence for each. According to the first and least controversial claim, emotions follow from moral judgments, such that witnessing immorality can lead to negative emotions and witnessing moral virtue can lead to positive ones. According to the second claim, emotions amplify moral judgments, for instance, by making immoral acts seem even more immoral. Finally, on the last claim, emotions can actually moralize nonmoral behaviors—that is, they give nonmoral acts a moral status. Although this claim seems to be the most intriguing one theoretically, empirical support for it is still very limited. In this review, we discuss research findings that are in line with each of these views, we highlight recurring themes across these three categories of evidence, and we identify some open questions and areas for future research. WIREs Cogn Sci 2013, 4:169–178. doi: 10.1002/wcs.1216 For further resources related to this article, please visit the WIREs website.